Statistical analysis of SHM passive sensing systems - Thiene,M; Khodaei,ZS; Aliabadi,MH (2016)
Structural Health Monitoring (SHM) techniques have gained an increased interest to be utilised alongside NDI techniques for aircraft maintenance. However, to take the SHM methodologies from the laboratory conditions to actual structures under real load conditions requires them to be assessed in terms of reliability and robustness. In this work, a statistical analysis is carried out for a passive SHM system capable of impact detection and identification. The sensitivity of the platform to parameters such as noise, sensor failure and in-service load conditions has been investigated and reported.